Electrokinetic Treatment Technique for the Improvement of Soft Clayey Soils - Abiodun, Abiola Ayopo (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
This study evaluates the effect of ionic solutions on the performance of electrokinetic (EK) treatment to improve the index and engineering properties of soft soils. The use of rare combinations of ionic solutions of calcium chloride (CaCl2) and sodium carbonate (Na2CO3), and conductive electrodes to stabilize the soft soil samples were introduced in the form of the laboratory model test tank. Atterberg limits, unconfined compression, one-dimensional swell and one-dimensional consolidation, wettingdrying, electrochemical, thermal, and microscopic tests were performed in terms of treatment duration, points of extraction in the soil from anode to cathode distances (dA↔E), and different combinations of ionic solutions such as calcium chloridedistilled water (CaCl2-DW), sodium carbonate-distilled water (Na2CO3-DW), and calcium chloride-sodium carbonate (CaCl2-Na2CO3). Electrokinetic, EK treatment caused a significant reduction in the cation exchange capacity (CEC), specific surface area (Sa ), plasticity index (PI), and volume change behavior of the treated soils using the rare combinations of ionic solutions of calcium chloride (CaCl2) and sodium carbonate (Na2CO3). The formation of the new compounds, calcium aluminosilicate hydrates (CASH), which were detected by differential thermal analysis (DTA), resulted in the strength gain of the electrokinetic, EK treated soils due to their newly formed aggregated and flocculated structure of the treated soil particles. The effect of changing electrode length (le ), on the performance of the electrokinetic, EK treatment on the engineering properties of soft soils were considered at different soil depths (ds ), and lengthwise anode to cathode distances (dA↔E). The tests were performed using changing electrode length ratios of 0.25lce, 0.50lce, 0.75lce, and 1.0lce. The study analyzed the test data obtained from the Atterberg limit and one-dimensional swelling iv tests at different extraction points in the test tank along with the anode to cathode distances (dA↔E), and vertical soil depth (ds ), within the treated soils. The design of experiments, DOE software program, was used to examine the effect of the electrochemical properties on the behavior of the treated soils and to determine the significant input factors for the electrokinetic, EK treatment of the soft soils. The analysis and optimization of the data obtained produced the threshold values to provide better soil strengthening using the design-expert software. The results of the design of experiment (DOE) model analysis revealed that the effect of changing electrode lengths, le on the plasticity index (PI) and swelling potential (SP) of the electrokinetic, EK treated soils, was significant. For a specific soil depth (ds ), the electrode length ratios (lce) of 0.50lce, and 0.75lce were significantly effective in reducing the plasticity index (PI) and the swelling potential (SP) of the electrokinetic, EK treated soils. Unlike other studies in the literature, the use of DOE analysis in the present study enabled the detection of the significant controlling factors in the electrokinetic, EK treatment and their interactive effects on the unconfined compressive strength (qu), plasticity index (PI), and the swelling potential (SP), enabling the practicing geotechnical engineers to compute precise engineering design models for large in situ geotechnical applications

ÖZ: Bu çalışma, yumuşak zeminlerin indeks ve mühendislik özelliklerini iyileştirmek için iyonik çözeltilerin elektrokinetik (EK) işleminin performansı üzerindeki etkisini değerlendirmektedir. Yumuşak toprak numunelerini stabilize etmek için kalsiyum klorür (CaCl2) ve sodyum karbonat (Na2CO3) iyonik çözeltilerinin nadir kombinasyonlarının ve iletken elektrotların kullanımı laboratuar modeli test tankı formunda tanıtıldı. Uygulama süresi, anottan katoda kadar topraktaki ekstraksiyon noktaları (dA↔E), ve kalsiyum klorür-damıtılmış su (CaCl2-DW), sodyum karbonatdamıtılmış su (Na2CO3-DW) ve kalsiyum klorür-sodyum karbonat (CaCl2-Na2CO3) gibi farklı iyonik çözelti kombinasyonları açısından Atterberg limitleri, serbest basınç, tek boyutlu şişme ve tek boyutlu konsolidasyon, ıslatma-kurutma, elektrokimyasal, termal ve mikroskobik testler yapılmıştır. Elektrokinetik, EK işlemi, kalsiyum klorür (CaCl2) ve sodyum karbonat (Na2CO3) gibi nadir iyonik çözelti kombinasyonları kullanarak işlenmiş toprakların katyon değişim kapasitesi (CEC), spesifik yüzey alanı (Sa ), plastisite indeksi (PI) ve hacim değişim davranışında önemli bir azalmaya neden oldu. Diferansiyel termal analiz (DTA) ile tespit edilen yeni bileşiklerin, kalsiyum alüminosilikat hidratların (CASH) oluşumu, elektrokinetik, EK ile muamele edilmiş toprakların, yeni oluşan kümelenmiş ve topaklanmış yapısı nedeni ile kuvvet kazanımı ile sonuçlanmıştır. Değişen elektrot uzunluğunun (le ), elektrokinetik performans üzerindeki etkisi, EK işleminin yumuşak zeminlerin mühendislik özellikleri üzerindeki etkisi, farklı toprak derinliklerinde (ds ) ve uzunlamasına anot-katot mesafelerinde (dA↔E) dikkate alınmıştır. Testler, 0.25lce, 0.50lce, 0.75lce ve 1.0lce 'lik değişen elektrot uzunluk oranları kullanılarak gerçekleştirildi. Çalışma, test tankında farklı ekstraksiyon noktalarında ve farklı anot katod mesafeleri (dA↔E) ve dikey toprak vi derinliklerinde (ds ) işlenmiş toprakda, Atterberg limiti ve tek boyutlu şişme testlerinden elde edilen test verilerini analiz etti. Deney tasarım, DOE yazılım programı, elektrokimyasal özelliklerin işlenmiş toprakların davranışı üzerindeki etkisini incelemek ve yumuşak toprakların elektrokinetik, EK işlemi için önemli girdi faktörlerini belirlemek için kullanılmıştır. Elde edilen verilerin analizi ve optimizasyonu, design-expert yazılımı kullanılarak daha iyi zemin güçlendirmesi sağlamak için eşik değerleri üretti. Deney tasarımı (DOE) model analizinin sonuçları, elektrot uzunluğu le'nin elektrokinetik, EK ile muamele edilmiş toprakların plastisite indeksi (PI) ve şişme potansiyeli (SP) üzerindeki etkisinin önemli olduğunu ortaya koymuştur. Spesifik bir toprak derinliği (ds ) için, 0.50lce ve 0.75lce elektrot uzunluğu oranları (lce), elektrokinetik, EK ile muamele edilmiş toprakların plastisite indeksini (PI) ve şişme potansiyelini (SP) azaltmada önemli ölçüde etkiliydi. Literatürdeki diğer çalışmalardan farklı olarak, mevcut çalışmada DOE analizinin kullanılması, elektrokinetik EK tedavisinde önemli kontrol faktörleri ve bunların serbest basınç mukavemeti, qu, plastisite indeksi (PI) ve şişme potansiyeli (SP) üzerindeki etkileşimli etkilerinin tesbiti uygulamadaki geoteknik mühendislerinin büyük arazi geoteknik uygulamalarında hassas mühendislik tasarım modellerini hesaplamasına olanak tanır
Doctor of Philosophy in Civil Engineering. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2020. Supervisor: Prof. Dr. Zalihe Sezai.
Keywords: Civil Engineering Department; Soil stabilization; Soil Mechanics; Geotechnical Engineering; Compressibility; electrodes; electrokinetic remediation; ionic solutions; numerical analyses; plasticity; strengthening; sodium carbonate; soft soils; swelling